Implementasi Pendidikan Islam Berbasis Minat Dan Bakat Perspektif Pembelajaran Berdiferensiasi - Siti Magfiroh, Vera; Hilman, Cecep (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the implementation of Islamic education based on students' interests and talents through a differentiated instruction approach. In the context of contemporary Islamic education, it is important to design a learning process that not only focuses on cognition but also accommodates the diverse potential, inclinations, and learning readiness of each individual. This study employs a qualitative approach using a literature review method, analyzing recent relevant literature from both accredited national journals and reputable international journals. The findings indicate that interest- and talent-based learning aligns with the principle of fitrah in Islam, which recognizes that every child has unique potential that must be developed holistically. Differentiated instruction has proven to be effective in enhancing student engagement, intrinsic motivation, and academic achievement when applied with the right strategies. However, its implementation requires teacher readiness, curriculum flexibility, and a supportive learning environment. This study recommends the importance of professional development for teachers and the development of a curriculum responsive to individual learning needs as part of the transformation of Islamic education that is just, inclusive, and relevant to the challenges of the 21st century.